ChemInform Abstract: A Regio‐ and Stereoselective ω‐Transaminase/Monoamine Oxidase Cascade for the Synthesis of Chiral 2, 5‐Disubstituted Pyrrolidines. Issue 33 (19th August 2014) - O'Reilly, Elaine; Iglesias, Cesar; Ghislieri, Diego; Hopwood, Jennifer; Galman, James L.; Lloyd, Richard C.; Turner, Nicholas J.
Abstract The chemoselective reductive cyclization of diones of type (I) in the presence of transaminase ATA113 is presented.